The relationship of CDK18 expression in breast cancer to clinicopathological parameters and therapeutic response - Barone, Giancarlo; Arora, Arvind; Ganesh, Anil; Abdel-Fatah, Tarek; Moseley, Paul; Ali, Reem; Chan, Stephen Y.T.; Savva, Constantinos; Schiavone, Kristina; Carmell, Natasha; Myers, Katie N.; Rakha, Emad A.; et al. (Impact Journals, 2018)
Background: Cyclin-Dependent Kinases (CDKs) are established anti-cancer drug targets and a new generation of CDK inhibitors are providing clinical benefits to a sub-set of breast cancer patients. We have recently shown that human CDK18 promotes efficient cellular responses to replication stress. In the current study, we have investigated the clinicopathological and functional significance of CDK18 expression levels in breast cancers. Methods: CDK18 protein expression was evaluated in 1650 breast cancers and correlated to clinicopathological parameters and survival outcomes. Similar analyses were carried out for genetic and transcriptomic changes in CDK18 within several publically available breast cancer cohorts. Additionally, we used a deactivated CRISPR/Cas9 approach to elucidate the molecular consequences of heightened endogenous CDK18 expression within breast cancer cells. Results: High CDK18 protein expression was associated with triple negative and basallike phenotype (p=0.021 and 0.027 respectively), and surprisingly, improved patient survival (n=1200, Log Rank 3.631, p=0.06). This was particularly significant in ER negative breast cancers (n=594, Log Rank 6.724, p=0.01) and those treated with chemotherapy (n=270, Log Rank 4.575, p=0.03). In agreement with these clinical findings, breast cancer cells genetically manipulated to express high levels of endogenous CDK18 exhibited an increased sensitivity to replication stress-inducing chemotherapeutic agents, as a consequence to defective replication stress signalling at the molecular level. Conclusions: These data reveal that CDK18 protein levels may predict breast cancer disease progression and response to chemotherapy, and provide further rationale for potential targeting of CDK18 as part of novel anti-cancer strategies for human cancers.